(untitled) (Bangladesh Journal of Botany, 2008)
Essential oil from roots of Vetiveria zizanioides (L.) Nash ex Small from Bangladesh was examined by gas chromatography mass spectrometry (GC-MS). Fourteen compounds were identified in root oil. The compositions of oil varied qualitatively and quantitatively. Key words: Vetiveria zizanioides, GC-MS analysis, Essential oil doi:10.3329/bjb.v37i2.1736 Bangladesh J. Bot. 37(2): 213-215, 2008 (December)